2021
DOI: 10.1111/bjhp.12519
|View full text |Cite
|
Sign up to set email alerts
|

Compliance without fear: Individual‐level protective behaviour during the first wave of the COVID‐19 pandemic

Abstract: Objectives. The outbreak of the COVID-19 pandemic required rapid public compliance with advice from health authorities. Here, we ask who was most likely to do so during the first wave of the pandemic.Design. Quota-sampled cross-sectional and panel data from eight Western democracies (Denmark, France, Germany, Hungary, Italy, Sweden, the United Kingdom, and the United States).Methods. We fielded online public opinion surveys to 26,508 citizens between 19 March and 16 May. The surveys included questions about pr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
153
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 161 publications
(193 citation statements)
references
References 44 publications
20
153
3
1
Order By: Relevance
“…In addition, not only a belief that protection behaviors were effective to reduce risks was necessary, a belief in one’s capabilities to perform these behaviors was pivotal. It was found that self-efficacy was more important than fear appeals for engaging protective behaviors during the pandemic, such that it itself constituted a pathway to compliance (Jørgensen et al, 2021 ). The current study demonstrated the different effects of the motivational determinants during the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, not only a belief that protection behaviors were effective to reduce risks was necessary, a belief in one’s capabilities to perform these behaviors was pivotal. It was found that self-efficacy was more important than fear appeals for engaging protective behaviors during the pandemic, such that it itself constituted a pathway to compliance (Jørgensen et al, 2021 ). The current study demonstrated the different effects of the motivational determinants during the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Because diseases are typically viewed as random accidents, the victims are seen as morally deserving of public help (Jensen and Petersen 2017). In the context of COVID-19, for example, prior research suggest that individuals higher in empathy are more likely to follow the advice of health authorities (Pfattheicher et al 2020), as are those fearful of the virus (Jørgensen et al 2021). In tandem, this implies that government responses may be supported from two, rather different, motivations: a fear-based motivation to protect the self and a prosocial motivation to protect others.…”
Section: Who Will Support Their Government's Response Against Covid-19?mentioning
confidence: 99%
“…Whereas previous research has sought to understand who supports stringent responses against COVID-19 or who are most motivated to comply with stringent restrictions (Jørgensen et al 2021; Van Bavel et al 2020), the present focus is instead on whether and from whom national governments during a massive crisis can foster support for the particular set of policies that each government promotes as necessary. Overall, the results show that this is indeed possible and we document relatively high support for each government's response against COVID-19.…”
mentioning
confidence: 99%
“…Existing evidence from the current and previous pandemics shows that trends in compliance can differ markedly across groups (Jørgensen et al, 2021;Petherick et al, 2021;van der Weerd et al, 2011;Wright & Fancourt, 2020). For instance, in the UK, compliance decreased faster among younger age groups over the first five months of the COVID-19 pandemic in the UK (Wright & Fancourt, 2020).…”
Section: Introductionmentioning
confidence: 99%